Linear and nonlinear optical characterization of plasmonic nanostructures of gold nanorods and metasurfaces - MALDONADO CANTILLO, Melissa Esther (2017)
Particles with characteristic length less than one hundred nanometers are known as nanoparticles (NP). Dielectric and/or metallic nanoparticles have been investigated in the last decades based on their electrical, optical and magnetic properties. One of the most important aspects in the study of metal nanoparticles is the surface plasmon resonance (SPR), an effect that occurs at the metal-dielectric interface, where the dielectric is the material that hosts the nanoparticles. The shape, size, and choice of the metal are important factors for determining the response of the material and the control of these characteristics for specific applications. Configurations that lead to the production of materials or metamaterials with different features from those known in the current literature are intended for new technological applications. In this thesis, we studied samples of gold nanorods oriented in a thin-film of Polyvinyl alcohol (PVA), Nanorods in Cargille oil and Gold metasurfaces in a glass substrate. In a first work, the PVA film was mechanically stretched, producing gold nanorods anisotropically distributed. The high anisotropy implies in this case that the non-linear absorption increases about fifty-seven times in comparison to the isotropic sample. We reported for the first time in the scientific literature this effect. Our experimental results were corroborated through numerical simulations, leading to very good agreement. Based on our research we attribute that the increase in the nonlinear absorption is due to the presence of clusters of a specific nanorods number. We verify the inversion of the nonlinear refractive signal as a function of the polarization of the incident light, a condition by which our material becomes an optimal candidate for making ultra-fast polarization keys. In a second experiment, we did optical control of gold nanorods suspended in Cargille oil, by applying an electric field we measured its nonlinear optical properties. In a third work, we characterized metasurfaces of gold where the average separation between nanoparticles is estimated to be 0.6nm. The metamaterials were prepared by a self-assembly method. The linear refractive index can vary from 0.87 to 4.2. The properties of these metasurfaces lead to a negative nonlinear refractive index. Therefore, it is a material with high self-defocusing. We measured a nonlinear negative absorption index of β₂, corresponding to saturated absorption. The value of β₂ is considered typical when compared to other gold nanoparticles, while the value of n₂ is approximately two magnitude orders greater. We used incident laser pulses with 100fs and 800nm, using repetition rates of 20Hz, 1kHz and 76MHz. The experimental techniques used were conventional Z-scan and Beam Collimated Hartmann-Shack for the studies of nonlinear optics.